The Role Of Progestogens In Threatened And Idiopathic Recurrent Miscarriage - Arab H; Alharbi AJ; Oraif A; Sagr E; Al Madani H; Abduljabbar H; Bajouh OS; Faden Y; Sabr Y (Dove Medical Press, 2019)
Hisham Arab,1 Ahmed Jaber Alharbi,2 Ayman Oraif,3 Emad Sagr,4 Hana Al Madani,5 Hassan Abduljabbar,3 Osama Sadeak Bajouh,3 Yaser Faden,6 Yasser Sabr7 1Obstetrics and Gynecology Department, Dr. Arab Medical Center, Jeddah, Saudi Arabia; 2Obstetrics and Gynecology Department, Ibinsina Medical Private College, Jeddah, Saudi Arabia; 3Department of Obstetrics and Gynecology, King Abdulaziz University, Jeddah, Saudi Arabia; 4Obstetrics and Gynecology Department, The International Medical Center, Jeddah, Saudi Arabia; 5Obstetrics and Gynecology Department, Maternity Hospital – King Saud Medical City, Riyadh, Saudi Arabia; 6Department of Obstetrics and Gynecology, King Saud bin Abdulaziz University for Health Sciences – Ministry of National Guard Health Affairs, Jeddah, Saudi Arabia; 7Maternal Fetal Medicine Division, Department of Obstetrics and Gynecology, College of Medicine, King Saud University, King Khalid University Hospital, Riyadh, Saudi ArabiaCorrespondence: Hisham ArabObstetrics and Gynecology Department, Dr. Arab Medical Center, P.O. Box 17440, Jeddah 21484, Saudi ArabiaTel +966 12 2832111Email arab123@gmail.comAbstract: It is well known that progesterone plays a major role in the maintenance of pregnancy, particularly during the early stages, as it is responsible for preparing the endometrium for implantation and maintenance of the gestational sac. The management of pregnant women at risk of a threatened or idiopathic recurrent miscarriage is complex and critical. Therefore, a group of obstetricians and gynecologists practicing in Saudi Arabia gathered to update the 2014 Saudi guidelines for threatened and recurrent miscarriage management. In preparation, a literature review was conducted to explore the role of oral, vaginal, and injectable progestogens: this was used as a basis to develop position statements to guide and standardize practice across Saudi Arabia.Keywords: idiopathic recurrent miscarriage, progesterone, progestin, progestogen, Saudi Arabia, threatened miscarriage